Provincial tax rate adjustments in Canada - Ferede, Ergete; Dahlby, Bev; Adjei, Ebenezer (My University, 2013)
Changes to tax rates are important fiscal events in Canada. They affect the amount of taxes that Canadian households and businesses pay to governments,and the level of economic activity by affecting incentives to work, save, and invest. Thus it is important to understand what factors cause governments to increase or reduce their tax rates.A recent study by Ergete Ferede, Bev Dahlby, and Ebenezer Adjei sheds some light on some of the factors that determine the timing and direction of tax rate adjustments by provincial governments.
Keywords: tax rates; provincial governments